A thematic review on research data management in citizen science projects - Che Jaafar, Cik Ramlah; Mohammed Ghazali, Asmadi; Mad Khir Johari, Abdullah Sani (Journal of Islamic, Social, Economics and Development, 2026)
Citizen science (CS) has emerged as a globally recognized participatory approach to scientific inquiry, engaging non-professionals in data collection and analysis. As the volume and complexity of citizen-generated data grow, effective Research Data Management (RDM) becomes essential to ensure data quality, ethical governance, and long-term usability. Despite increasing attention, a gap remains in the consolidated understanding of how RDM is applied, evaluated, and discussed across diverse citizen science contexts. Therefore, this thematic review aims to explore current trends in RDM within CS projects, focusing on peer-reviewed literature published between 2021 and 2025. The study systematically searched the Scopus and Web of Science (WoS) databases and identified 26 relevant journal articles, which were analyzed using ATLAS.ti 24. Four key themes emerged: (i) increasing emphasis on data quality assurance and validation; (ii) movement toward ethical data governance and open science alignment; (iii) integration of digital infrastructures for scalable data management; and (iv) capacity building and empowerment through data literacy and participation. These findings reveal a shift from informal, ad hoc data practices to more structured, ethical, and community-informed approaches in managing CS data. This review contributes a timely synthesis of evolving RDM practices in CS projects and offers practical implications for researchers, practitioners, and policymakers. It also identifies future research opportunities, including context-specific applications, digital ethics, and inclusive frameworks for participatory data stewardship.